Efficacy and safety of eslicarbazepine acetate as add‐on treatment in patients with focal‐onset seizures: Integrated analysis of pooled data from double‐blind phase III clinical studies. Issue 1 (6th August 2012) - Gil‐Nagel, António; Elger, Christian; Ben‐Menachem, Elinor; Halász, Peter; Lopes‐Lima, José; Gabbai, Alberto A.; Nunes, Teresa; Falcão, Amílcar; Almeida, Luis; da‐Silva, Patrício Soares
Summary Purpose: To evaluate the efficacy and safety profile of eslicarbazepine acetate (ESL) added to stable antiepileptic therapy in adults with partial‐onset seizures. Methods: Data from 1, 049 patients enrolled from 125 centers, in 23 countries, in three phase III double‐blind, randomized, placebo‐controlled studies were pooled and analyzed. Following a 2‐week titration period, ESL was administered at 400 mg, 800 mg, and 1, 200 mg once‐daily doses for 12 weeks. Key Findings: Seizure frequency was significantly reduced with ESL 800 mg (p < 0.0001) and 1, 200 mg (p < 0.0001) compared to placebo. Median relative reduction in seizure frequency was, respectively, 35% and 39% (placebo 15%) and responder rate was 36% and 44% (placebo 22%). ESL was more efficacious than placebo regardless of gender, geographic region, epilepsy duration, age at time of diagnosis, seizure type, and number and type of concomitant antiepileptic drugs (AEDs). Incidence of adverse events (AEs) and AEs leading to discontinuation were dose dependent. AEs occurred mainly during the first weeks of treatment, with no difference between groups after 6 weeks. Most common AEs (>10% patients) were dizziness, somnolence, and headache. The incidence of AEs in ESL groups compared to placebo was generally consistent among different subpopulations. Significance: Once‐daily ESL 800 mg and 1, 200 mg showed consistent results across all efficacy and safety end points. Results were independent of study population characteristics and type and number of concomitant AEDs.